Application of Cement-Based Carbon Fiber Material in Construction of Building Durability - Qiuhong Li; Yinlong Li; Yong Zhang; Yongrui Han (International Journal of Analytical Chemistry)
In order to solve the problem of drying shrinkage of cement-based carbon fiber materials in the early stage of hardening, the author proposes the application of cement-based carbon fiber materials in the construction of building durability. The author uses a self-designed fast ring test method to test and study the drying shrinkage performance of cement-based carbon fiber materials in the early stage of hardening. The results showed that the addition of MP-I and MP-II fibers, which can significantly reduce shrinkage cracking in plastic concrete, has little effect on preventing the shrinkage and cracking of concrete in the early stage of hardening. Mixed with a certain amount of steel fiber, carbon fiber, MH-I, and MPH-I hardened anticrack fiber, all have a better effect on preventing early water loss and drying shrinkage of hardening. The MH-I and MPH-I hardening anticracking fibers have an economical and feasible dosage, and the early water loss shrinkage and crack reduction rates of concrete hardening are 71.2% and 79.0%, respectively. MH-I fibers have no anticracking effect in the plastic stage and are only suitable for shrinkage and crack prevention of concrete in the early stage of hardening, while MPH-I hardened anticrack fibers have a 100% crack-reducing effect in the plastic stage, it is an engineering fiber material that can simultaneously prevent the plasticity and early hardening of concrete from shrinkage and cracking. The application of MPH-I hardened anticrack fiber is of great significance to improve the quality of structural engineering.